CONCEPTUAL FRAMEWORK FOR THE BEST PRACTICES OF BEHAVIOR-BASED SAFETY PERFORMANCE EVALUATION IN SMALL AND MEDIUM ENTERPRISES (SMES) - Awang, Zainudin; Rahlin, Nor Azma; Afthanorhan, Asyraf (Journal of Applied Engineering Science, 2019)
Employee in small manufacturing enterprise (SMEs) industry suffer high rates of industrial accident than large company as reflected eight times more fatal accidents and 50 % of injuries more likely to occur. With the rising importance of the SMEs, ensuring high levels of safety in SMEs remains a significant issue.  This study was undertaken to explore the factors influencing the behaviour-based safety performance in the small medium enterprise. A comprehensive review of the safety literature enabled the invention of the constructs, and items that supported a conceptual behavior-based safety performance evaluation framework.  A conceptual framework was adopted based on integration Theory Planned Behavior and Social Exchange Theory. Thus, this study proposed four constructs of behavior-based safety performance evaluation, namely, work ownership and Islamic work ethics, safety climate, and behavior-based safety performance.  The best practice of behavior-based safety performance evaluation conceptual framework is proposed for implementation by the SMEs Entrepreneur and practitioner to proactively monitor and manage SMEs safety in the future. The framework will be tested empirically using data collected from SMEs companies in Malaysia. This conceptual framework is one of the alternatives to effectively evaluate safety performance in SMEs, particularly in the Malaysian context.
Keywords: Islamic work ethics; behavior-based; small medium enterprises; work ownership; employee safety climate; safety performance